The Analysis of Teachers’ Talk during Classroom Interaction in English Class Using Flint Category - Sani, Fitri Hidayati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Interaction in the classroom has been a real concern in teaching English. The configuration in which language learning proceeds is one that encourages student participation, collaboration, and communication among students as well as between students and teachers. This study used the FLINT category at junior high schools in Padang with the goal of analyzing teacher talk during classroom interaction in English lessons. This research is descriptive in nature. Teachers from junior high schools were chosen as participants in this study. During the teaching and learning process, the researcher observed how teachers and students interacted. The researcher collected all data from observation (by means of video recording, audio recording, and field notes). Then, transcribe and code the data. The researcher identified teachers’ talk types based on FLINT analysis. According to the findings of this study, the teacher continued to control the conversation in class. The teacher was more caught up in the class than the students were. The majority of the student talking time was devoted to answering the teacher's questions and responding. To teach her / his students, the teacher used direct influence almost as much as indirect one.